Qualitative properties of traditionally produced dry fermented sausages from meat of the autochthonous Mangalitsa pig breed. (September 2019) - Parunovic, N; Savic, R; Radovic, C
Abstract: The interest in autochthonous meat products from local pig breeds managed in comprehensive, sustainable breeding programs is expanding in Europe. Dry fermented sausages in Serbia and other southern European countries are highly appreciated food specialties. It is, therefore, desirable that study attempts to improve the quality of food and the security of traditional, dry sausages will result in products that are of higher added value and have quality standards that best meet the needs of contemporary customers. Meat and meat products from traditional pig breeds usually have an excellent public and media reputation, and are often regarded as better than the meat and meat products of conventionally raised pigs and crossbreed pigs. Traditional, dry fermented sausages, with their characteristic chemical contents and sensory properties, can be produced with suitable proportions of meat and backfat from the indigenous Mangalitsa pig breed. These outcomes should hopefully encourage the sustainable breeding of endangered Mangalitsa pigs, as there are market opportunities for kulen and sremska sausages.